Composite diaphragm and preparation method and application thereof

CN117458083BActive Publication Date: 2026-10-27蓝固(淄博)新能源科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311577323.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-23
Publication Date
2026-10-27
Estimated Expiration
2043-11-23

AI Technical Summary

Technical Problem

但此方法制备的电解质膜步骤仍较为复杂,另外,由于电解质膜的吸液率大于360%,严重影响了电解质的机械性能,组装到电池中后,充放电时发生的电极体积变化、锂枝晶生长等容易破坏电解质膜的完整性,进而引发安全事故

Benefits of technology

[0053]另外,本发明提供的上述复合隔膜的制备方法简便,以聚醚砜膜为基底,通过常规的成膜处理手段将改性聚酰亚胺膜复合在聚醚砜膜表面后,再通过真空烘干去除溶剂实现造孔目的后,即可得到具有较大孔隙率的复合隔膜。该制备方法中无需昂贵的仪器设备,工艺成本低廉,容易操作,简单易行,具有非常广阔的应用前景,有利于实现大规模工业化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117458083B_ABST
    Figure CN117458083B_ABST
Patent Text Reader

Abstract

The application provides a composite diaphragm and a preparation method and application thereof, and the composite diaphragm comprises a polyether sulfone film layer and a modified polyimide film layer arranged on the surface of the polyether sulfone film layer, and the modified polyimide film layer is a norbornene group terminated polyimide film layer or a polyamino bismaleimide film layer. The application uses the polyether sulfone film layer with excellent mechanical properties and good dimensional stability as a substrate, and the modified polyimide film layer with good wettability and high temperature resistance is compounded on the surface of the polyether sulfone film layer, so that the prepared composite diaphragm has excellent high temperature dimensional stability, wettability, flame retardancy and mechanical properties. According to the test, the lithium ion battery using the composite diaphragm provided by the application as a diaphragm does not have the phenomena of explosion or combustion and the like under the high temperature environment of 300 DEG C for 4 hours, which indicates that the diaphragm has excellent high temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of secondary batteries, specifically to a composite separator, its preparation method, and its application. Background Technology

[0002] Secondary batteries, with their numerous advantages such as high energy density, high discharge voltage, no memory effect, and long cycle life, have become a typical representative of next-generation large-scale energy storage and power batteries. Currently, they are widely used in mobile phones, laptops, power tools, drones, and electric vehicles. However, with the continuous increase in battery energy density and capacity, battery safety issues are becoming increasingly prominent. In particular, battery combustion and explosions in electric vehicles have caused significant personal injury and property damage, drawing considerable attention from the scientific research and industrial communities. Therefore, improving the safety of lithium (sodium) ion batteries is urgently needed.

[0003] As is well known, the separator and electrolyte are crucial components of lithium-ion batteries. The separator separates the positive and negative electrodes, preventing short circuits caused by contact between them; the electrolyte is the medium for lithium ion migration between the electrodes. Currently, commercially available lithium-ion batteries commonly use polyolefin separators such as polyethylene and polypropylene. However, polyolefin separators have poor heat resistance; for example, the melting temperature of polyethylene separators is only 130°C. When the battery temperature exceeds this, the separator will shrink rapidly, potentially leading to short circuits, fires, or even explosions. Furthermore, most liquid lithium-ion batteries currently use liquid carbonate-based electrolytes. These electrolytes have low boiling points and are easily flammable, contributing significantly to safety hazards in lithium-ion batteries. Therefore, developing novel high-temperature resistant, non-flammable polymer electrolyte systems to replace flammable liquid carbonate electrolytes and polyolefin separators can significantly improve the safety and reliability of lithium-ion batteries.

[0004] Gel polymer electrolytes consist of a polymer matrix and a small amount of electrolyte. Compared to solid polymer or inorganic solid electrolytes, gel polymer electrolytes exhibit higher ionic conductivity, better electrode / electrolyte interface contact, and non-flow properties. Furthermore, although gel polymer electrolytes contain a small amount of electrolyte, most of this electrolyte is fixed between the polymer molecular chains, thus preventing free volatilization and reducing the risk of combustion. Additionally, selecting a suitable polymer matrix can significantly improve the mechanical properties and heat resistance of gel polymer electrolytes.

[0005] Polyimide, a polymer containing polyamide rings in its main chain, is one of the organic polymer materials with excellent comprehensive properties. It has a high temperature resistance exceeding 350℃, a long-term operating temperature range of 200-300℃, and extremely high insulation performance. Compared with traditional separators, polyimide separators offer advantages such as better high-temperature resistance and improved battery safety. Therefore, it has attracted considerable attention from researchers.

[0006] Patent CN 111430792A discloses a composite gel solid electrolyte, its preparation method, and an all-solid-state lithium-ion battery. This method first prepares a polyimide precursor (polyamic acid) gel using 2,2'-dimethylbenzidine, 3,3',4,4'-biphenyltetracarboxylic dianhydride, N-methyl-2-pyrrolidone, 3-aminopropyltrihexyloxysilane, lithium bis(trifluoromethanesulfonyl)imide, and acetic anhydride. This precursor is then mixed with a lithium-based gel composed of lithium perchlorate, glycerol, deionized water, and polyacrylamide to prepare a high-temperature resistant gel electrolyte system. The polyimide gel electrolyte prepared by this invention can reduce longitudinal and transverse thermal shrinkage while maintaining excellent mechanical properties and high puncture strength; effectively increasing the shrinkage initiation temperature, deformation temperature, and rupture temperature; and simultaneously improving ionic conductivity and lithium-ion transference number. However, this preparation method involves the separate preparation of two gels, each with complex components, making the preparation process very cumbersome and unsuitable for large-scale mass production.

[0007] Patent CN 106328862A discloses a method for preparing a cross-linked polyimide gel polymer electrolyte membrane. In this method, polyimide is first dissolved in an aprotic solvent and cross-linked with an amino-containing silane coupling agent, then cured into a membrane. The resulting membrane is then placed in an electrolyte solution, allowing it to absorb liquid and swell. However, the preparation process of this electrolyte membrane is still relatively complex. Furthermore, because the electrolyte membrane's liquid absorption rate is greater than 360%, it severely affects the mechanical properties of the electrolyte. After assembly into a battery, electrode volume changes and lithium dendrite growth during charging and discharging can easily damage the integrity of the electrolyte membrane, potentially leading to safety accidents. Summary of the Invention

[0008] In view of this, the purpose of this invention is to provide a composite diaphragm, its preparation method, and its application. The composite diaphragm has a simple preparation process and excellent overall performance, exhibiting good high-temperature dimensional thermal stability, high-temperature mechanical properties, wettability, as well as high porosity and liquid retention rate.

[0009] To achieve this objective, the present invention adopts the following technical solution:

[0010] In a first aspect, the present invention provides a composite membrane, comprising a polyethersulfone membrane layer and a modified polyimide membrane layer disposed on the surface of the polyethersulfone membrane layer;

[0011] The modified polyimide film is a norbornene-terminated polyimide film or a polyaminobismaleimide film.

[0012] It should be noted that, due to differences in preparation methods, the interior of the polyethersulfone film may or may not contain an impregnated modified polyimide film layer.

[0013] Preferably, the mass ratio of the modified polyimide film to the polyethersulfone film is (0.1 to 1000):1.

[0014] Preferably, the porosity of the composite membrane is 40-95%.

[0015] Preferably, the pore size of the composite membrane is 0.01 to 10 μm.

[0016] Preferably, the thickness of the composite diaphragm is 1–1000 μm.

[0017] Secondly, the present invention provides a method for preparing the composite separator involved in the above technical solution, comprising the following steps:

[0018] S1: Mix the modified polyamic acid with a solvent to obtain a modified polyamic acid solution;

[0019] The modified polyamic acid is norbornene-terminated polyamic acid or polyaminoamic acid;

[0020] S2: The modified polyamic acid solution is composited onto the surface of a polyethersulfone membrane through a film-forming treatment. The resulting product is then subjected to imidization treatment and vacuum drying to obtain a composite membrane.

[0021] The present invention also provides another method for preparing the composite membrane involved in the above technical solution, comprising the following steps:

[0022] S1: Mix the modified polyimide with a solvent to obtain a modified polyimide solution;

[0023] The modified polyimide is a norbornene-terminated polyimide or a polyaminobismaleimide;

[0024] S2: The modified polyimide solution is laminated onto the surface of the polyethersulfone membrane through a film-forming treatment, and then vacuum dried to obtain a composite membrane.

[0025] Preferably, the modified polyamic acid has a molecular weight of 500 to 100,000 g / mol.

[0026] Preferably, the mass fraction of the solute in the modified polyamic acid solution is 1-40 wt%.

[0027] Preferably, the modified polyimide has a molecular weight of 500 to 100,000 g / mol.

[0028] Preferably, the mass fraction of the solute in the modified polyimide solution is 1–40 wt%.

[0029] Preferably, the solvent involved in the modified polyamic acid solution or modified polyimide solution is selected from any one or more of N,N-dimethylacetamide, N-methylpyrrolidone, N,N-dimethylformamide, sulfolane, acetonitrile, tetrahydrofuran, acetone, toluene, chloroform, or methanol.

[0030] Preferably, the mixing temperature in the above two preparation methods is 50–150°C.

[0031] Preferably, the film-forming treatment method described in the above two preparation methods is selected from any one of electrospinning, spraying, blade coating, spin coating, hot pressing, gel stretching, or sol-gel methods.

[0032] Preferably, the imidization treatment is performed at a temperature of 200–300°C for a time of 0.1–120 h.

[0033] Preferably, in the two preparation methods described above, the vacuum drying temperature is 40–100°C and the drying time is 0.1–48 h.

[0034] Thirdly, the present invention provides a liquid secondary battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte; wherein the separator is a composite separator involved in the above-mentioned technical solution.

[0035] Preferably, the liquid secondary battery is selected from any one of lithium (sodium) ion batteries, lithium (sodium) metal batteries, or lithium (sodium) sulfur batteries.

[0036] Preferably, the positive electrode includes a positive electrode current collector and an active material of the positive electrode.

[0037] Preferably, the negative electrode includes a negative electrode current collector and an active material of the negative electrode.

[0038] Preferably, the active material of the positive electrode is selected from any one of high-nickel single crystal 9055, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, sodium iron phosphate, sodium titanium phosphate, sodium iron pyrophosphate, sodium iron sulfate, sodium iron manganese phosphate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium fluorovanadium phosphate, sodium vanadium phosphate, carbon sulfur, or polyacrylonitrile / sulfur.

[0039] Preferably, the positive current collector is aluminum foil.

[0040] Preferably, the active material of the negative electrode is selected from any one of lithium metal, graphite, silicon carbide, lithium titanate, hard carbon, sodium vanadium phosphate, sodium titanium phosphate, or sodium metal.

[0041] Preferably, the negative electrode current collector is copper foil.

[0042] Fourthly, the present invention provides a solid-liquid hybrid secondary battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte; the separator is the composite separator involved in the above-mentioned technical solution; the positive electrode comprises a positive electrode current collector, a positive electrode active material, and a solid electrolyte; the negative electrode comprises a negative electrode current collector, a negative electrode active material, and a solid electrolyte.

[0043] Preferably, the solid-liquid hybrid secondary battery is selected from any one of sodium (lithium) ion batteries, sodium (lithium) metal batteries, or sodium (lithium) sulfur batteries.

[0044] Preferably, the active material of the positive electrode is selected from any one of sodium iron phosphate, sodium titanium phosphate, sodium iron pyrophosphate, sodium iron sulfate, sodium iron manganese phosphate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium fluorovanadium phosphate, sodium vanadium phosphate, lithium cobalt oxide, lithium manganese oxide, NCM series, high nickel 9055, carbon sulfur, or polyacrylonitrile / sulfur.

[0045] Preferably, the positive current collector is aluminum foil.

[0046] Preferably, the active material of the negative electrode is selected from any one of sodium metal, sodium vanadium phosphate, sodium titanium phosphate, lithium metal, lithium titanate, graphite, silicon carbide, and hard carbon.

[0047] Preferably, the negative electrode current collector is any one of aluminum foil, copper foil, or titanium foil.

[0048] Preferably, the solid electrolytes in the positive and negative electrodes are each independently any one of LLTO, LLZO, NZSP, cryolite, boehmite, or β-alumina.

[0049] Among them, LLTO refers to lithium lanthanum titanium oxide solid electrolyte, LLZO refers to lithium lanthanum zirconium oxide solid electrolyte, and NZSP refers to sodium zirconium silicon phosphorus oxide solid electrolyte.

[0050] It should be noted that the solid electrolyte can be mixed into the positive (or negative) electrode slurry, or it can be directly coated onto the positive (or negative) electrode sheet. Compared with the prior art, the beneficial effects of the present invention are:

[0051] This invention provides a composite membrane comprising a polyethersulfone (PES) membrane layer and a modified polyimide membrane layer disposed on the surface of the PES membrane layer. The PES membrane possesses excellent mechanical properties, with a tensile strength of 84.3 MPa, a flexural modulus of 2.65 GPa, an elongation at break of 5–6%, and a notched impact strength of 91 J / m. Compared to polyolefin membranes, PES membranes exhibit better melt processability and lower melt viscosity, lower molding shrinkage (only about 0.6%), better dimensional stability, and excellent resistance to inorganic chemicals and solvents such as acids and alkalis. However, they are not resistant to highly polar organic solvents such as ketones, esters, halogenated hydrocarbons, and dimethyl sulfoxide. At high temperatures, these organic solvents can induce stress cracking due to residual stress in the PES membrane. Therefore, this invention incorporates a modified polyimide membrane layer on the surface of the PES membrane layer. Because traditional condensation-type polyimides are prone to generating uneven voids during preparation, this invention employs addition-polymerized polyimides. These are low-molecular-weight polyimides with unsaturated end groups. During application, addition polymerization is performed through these unsaturated end groups, resulting in enhanced plasticity and electrochemical performance. The main types are polybismaleimide and norbornene-terminated polyimides. It is important to note that when polyimides are assembled with positive and negative electrode plates into a battery, the active functional groups on the polyimide surface, under the wetting of the electrolyte, undergo initial bonding with the solid electrolyte coated on the electrode surface through van der Waals forces and hydrogen bonds. This significantly enhances the adhesion between the positive electrode material and the separator, and between the separator and the negative electrode material. This reduces the adverse effects on battery performance caused by gas voids formed between the separator and electrode due to gas generation, such as micro-short circuits, electrolyte decomposition, and metal deposition.

[0052] Characterization revealed that the composite separator has a thickness of 1–1000 μm, a porosity of 40–95%, and a pore size of 0.01–10 μm. Furthermore, testing showed that the composite separator exhibited a deformation of less than 0.003% after one month under high load at 300°C, demonstrating excellent high-temperature dimensional stability, making it suitable for use in secondary batteries operating in special high-temperature environments. Its electrolyte retention rate is 200–1000%, exhibiting excellent wettability and addressing the viscosity requirements of electrolytes in secondary batteries to some extent. With a limiting oxygen index greater than 40, it possesses excellent flame retardancy, significantly improving the safety performance of secondary batteries. Its tensile strength is above 95 MPa, demonstrating excellent mechanical properties. Taking lithium-ion batteries as an example, it can effectively suppress and resist lithium dendrite puncture (as tested in lithium-lithium deposition experiments), thereby avoiding short circuits caused by lithium dendrite punctures in traditional polyolefin separators.

[0053] Furthermore, the preparation method of the composite membrane provided by this invention is simple. Using a polyethersulfone membrane as a substrate, a modified polyimide membrane is laminated onto the surface of the polyethersulfone membrane through conventional film-forming methods. Then, the solvent is removed by vacuum drying to achieve pore formation, resulting in a composite membrane with high porosity. This preparation method requires no expensive equipment, has low processing costs, is easy to operate, and has broad application prospects, facilitating large-scale industrial production. Attached Figure Description

[0054] Figure 1 This is a scanning electron microscope image of the composite porous membrane obtained in Example 1;

[0055] Figure 2 This is a comparison of the dimensional thermal stability of the composite porous membrane obtained in Example 1 and the commercial PP membrane at 180°C.

[0056] Figure 3 This is a comparison of the wetting performance of the composite porous membrane obtained in Example 1 and the commercial PP membrane in a commercial non-aqueous electrolyte (EC / DMC = 1:1 LIPF6-1M).

[0057] Figure 4 The graph shows the cycle performance of a high-voltage lithium metal battery using the composite porous membrane obtained in Example 1 as the separator at 1C.

[0058] Figure 5 The above is a charge-discharge curve of a high-voltage lithium metal battery using the composite porous membrane obtained in Example 3 as the separator.

[0059] Figure 6 The graph shows the long-cycle performance of a high-voltage sodium metal battery using the composite porous membrane obtained in Example 12 as the separator.

[0060] Figure 7 The graph shows the long-cycle performance of a high-voltage sodium-ion battery using the composite porous membrane obtained in Example 13 as the separator. Detailed Implementation

[0061] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0062] Currently, the main separator materials for batteries are single-layer microporous membranes of polyethylene (PE) and polypropylene (PP), as well as their multilayer composite microporous membranes. These materials are made by uniaxial stretching and have disadvantages such as narrow and elongated pores, low lateral strength, and complex manufacturing processes, which limits their widespread use.

[0063] On the other hand, this type of polyolefin separator has a low melting temperature. In cases of overcharging or improper use, if the battery temperature exceeds 160°C due to internal or external overheating, the polyolefin separator may shrink or melt, causing a short circuit between the positive and negative electrodes. This poses a risk of battery combustion or explosion, seriously threatening the user's life. Therefore, power lithium batteries require separators that possess not only the basic performance of ordinary separators but also superior high-temperature resistance. Currently, more and more power lithium battery manufacturers require separators to have high-temperature heat shrinkage resistance up to 150°C. Among conventional polyolefin separators, polyethylene separators have a melting point of 130°C; exceeding this point will cause the separator to melt. Polypropylene separators have a melting point of 163°C; at 150°C, the separator will shrink by more than 30%. Therefore, traditional polyolefin separators cannot meet the higher demands of power lithium batteries. Furthermore, polyolefin separators have poor electrolyte wetting properties, potentially leading to "dry zones" inside the battery, significantly affecting the battery's cycle stability.

[0064] To address the potential safety hazards of traditional polyolefin separators, such as poor high-temperature resistance, low mechanical strength, and easy shrinkage due to heat leading to short circuits; to solve the harsh environmental requirements in the preparation of separators for lithium-sodium ion batteries; and to effectively reduce the high processing costs and environmental pollution associated with battery separators, this invention provides a composite separator, comprising a polyethersulfone film layer and a modified polyimide film layer disposed on the surface of the polyethersulfone film layer.

[0065] In this invention, the polyethersulfone (PES) film layer serves as the substrate, and its source is not particularly limited; commercially available aqueous PES film is sufficient. The aqueous PES film possesses high mechanical properties among thermoplastics, with a tensile strength of 84.3 MPa, a flexural modulus of 2.65 GPa, an elongation at break of 5–6%, and a notched impact strength of 91 J / m. Compared to traditional polyolefin separators, aqueous PES film exhibits better melt processability and lower melt viscosity, lower molding shrinkage (only about 0.6%), better dimensional stability, and excellent resistance to inorganic chemicals and solvents such as acids and alkalis. However, it is not resistant to highly polar organic solvents, such as ketones, esters, halogenated hydrocarbons, or dimethyl sulfoxide. Therefore, this invention incorporates a modified polyimide film layer on the surface of the PES film layer to address the problems encountered by PES film in highly polar organic solvent environments.

[0066] Traditional condensation-type aromatic polyimides are prepared by reacting aromatic diamines with aromatic dianhydrides, aromatic tetracarboxylic acids, or dialkyl esters of aromatic tetracarboxylic acids. Because the synthesis of condensation-type polyimides is carried out in high-boiling-point aprotic polar solvents such as dimethylformamide and N-methylpyrrolidone, and polyimide composites are typically manufactured using prepreg molding processes, these high-boiling-point aprotic polar solvents are difficult to completely evaporate during prepreg preparation. Furthermore, volatiles are released during the polyamic acid cyclization (imidization), resulting in uneven porosity in the composite material and making it difficult to obtain high-quality composites with uniform porosity.

[0067] To overcome the aforementioned drawbacks of traditional condensation-type polyimides, this invention employs addition-polymerized polyimides composited on the surface of a polyethersulfone film, primarily composed of polybismaleimide and norbornene-terminated polyimide. Its key feature is the presence of low molecular weight polyimides with unsaturated end groups. During application, addition polymerization occurs through these unsaturated end groups, resulting in enhanced plasticity and electrochemical performance. It should be noted that polyimide itself is a high-end insulating industrial raw material, serving as an excellent electronic insulator for both positive and negative electrodes. The presence of its amide groups facilitates ion conduction and rapid wetting of the electrolyte solution. Furthermore, polyimide can withstand temperatures up to 350°C, allowing it to function normally in high-temperature environments when used as a separator in lithium-ion batteries. It also prevents thermal shrinkage during rapid battery temperature increases, avoiding short circuits between the positive and negative electrodes.

[0068] In summary, the composite separator provided by the present invention includes a polyethersulfone film layer and a modified polyimide film layer disposed on the surface of the polyethersulfone film layer. The modified polyimide film layer is a norbornene-terminated polyimide layer or a polyaminobismaleimide layer. In the present invention, the mass ratio of the modified polyimide film layer to the polyethersulfone film layer is (0.1–1000):1, preferably (1–500):1, and more preferably (10–100):1.

[0069] The composite membrane has been tested and found to have a thickness of 1–1000 μm, which can be 1 μm, 10 μm, 50 μm, 100 μm, 200 μm, 500 μm, 800 μm or 1000 μm, preferably 200–600 μm; a porosity of 40–95%, which can be 40%, 50%, 60%, 70%, 80% or 90%, preferably 60–95%; and a pore size of 0.01–10 μm, which can be 0.01 μm, 0.05 μm, 1 μm, 2 μm, 5 μm, 8 μm or 10 μm, preferably 0.5–5 μm.

[0070] In this invention, the point values ​​listed above are merely for illustrative purposes and are not limited thereto. Other point values ​​within their numerical range are also applicable, but to avoid complexity, they will not be described in detail.

[0071] In this invention, when modifying the surface of a polyethersulfone (PES) film with modified polyimide (PI), the composite method of PI and PES includes film-forming methods well known to those skilled in the art. The PI can be introduced in the form of modified polyamic acid or modified polyimide. When the PI is introduced in the form of modified polyamic acid, it needs to be imidized at high temperature. Therefore, the method of introducing PI depends on the chemical stability (i.e., the difficulty of chemical modification) of the composite film.

[0072] In some embodiments of the present invention, when the PI is introduced in the form of modified polyamic acid, the method for preparing the composite separator includes the following steps:

[0073] S1: Mix the modified polyamic acid with a solvent to obtain a modified polyamic acid solution;

[0074] The modified polyamic acid is norbornene-terminated polyamic acid or polyaminoamic acid;

[0075] S2: The modified polyamic acid solution is composited onto the surface of a polyethersulfone membrane through a film-forming treatment. The resulting product is then subjected to imidization treatment and vacuum drying to obtain a composite membrane.

[0076] According to the present invention, modified polyamic acid is first mixed with a solvent to obtain a modified polyamic acid solution. In the present invention, the modified polyamic acid is norbornene-terminated polyamic acid or polyaminoamic acid. The present invention does not impose any particular limitation on the preparation method of norbornene-terminated polyamic acid or polyaminoamic acid, and can be prepared according to methods well known to those skilled in the art. The norbornene-terminated polyamic acid is prepared by the following method: S1: Norbornene anhydride is refluxed with ethanol to obtain norbornene monoester monoacid; S2: The norbornene monoester monoacid undergoes two-step chemical reactions S21 and S22; in the first step reaction S21, the norbornene monoester monoacid is dissolved in an organic solvent and then reacted with an aromatic diamine; in the second step reaction S22, the product obtained in the first step is reacted with carboxylic anhydride in a solution containing pyridine (pyridine acts as a stabilizer and catalyst, participating in the reaction but not remaining in the product) to obtain norbornene-terminated polyamic acid. In step S1, the amount of ethanol is preferably 10 to 20 times that of norbornene anhydride, more preferably 12 to 15 times. In step S1, the temperature of the chemical reaction is 55 to 65°C, preferably 60°C, and the time is 4 to 12 hours, preferably 8 to 10 hours. In step S21, the molar ratio of norbornene monoester monoacid to aromatic diamine is preferably (1.2 to 3):1, more preferably (1.5 to 2):1; the molar ratio of acetic anhydride to norbornene monoester monoacid is preferably (2 to 4):1, more preferably (2.5 to 3):1; the molar ratio of acetic anhydride to pyridine is preferably (1.5 to 3):1, more preferably (2 to 2.5):1. In step S21, the organic solvent is any one of dimethylformamide (DMF), dimethylacetamide (DMAc), or N-methylpyrrolidone (NMP), or a mixture of any of these in any proportion. The mass ratio of the organic solvent to norbornene monoester monoacid is (2-4):1. In some embodiments of the present invention, the reaction conditions for S1 are as follows: after the norbornene monoester monoacid is dissolved in the organic solvent, an aromatic diamine is added under nitrogen protection, and the reaction is stirred at room temperature for 1-3 hours; the reaction conditions for S2 are as follows: after S21 is completed, acetic anhydride and pyridine are added, and the reaction is heated to 120-180°C for 2-6 hours. Preferably, the reaction also includes post-treatment: after cooling the reaction solution obtained in S22 to room temperature, it is poured into deionized water, a yellow powdery solid precipitates out, and after filtration, the filter cake is dried in a vacuum oven at a temperature of 80-120°C, preferably 100-110°C, for 10-24 hours. The volume of deionized water is 5-15 times the total volume of the reaction solution, preferably 8-12 times.

[0077] The preparation method of polyaminoamic acid can be directly referred to the preparation method of norbornene-terminated polyamic acid described above. The only difference is that the norbornene anhydride is replaced with aminated bismaleic anhydride. The aminated bismaleic anhydride is obtained by treating bismaleic anhydride with an amination reagent. The amination reagent can be selected from organic (primary, secondary, tertiary) amines, quaternary ammonium salts, or hydroxylamines, etc. The other steps and parameters can remain the same.

[0078] In this invention, the room temperature refers to a temperature of "25-30°C", preferably 25°C.

[0079] In this invention, the molecular weight of the modified polyamic acid is preferably 500–100,000 g / mol, more preferably 2,000–10,000 g / mol. The solvent includes, but is not limited to, any one or more of N,N-dimethylacetamide, N-methylpyrrolidone, N,N-dimethylformamide, sulfolane, acetonitrile, tetrahydrofuran, acetone, toluene, chloroform, or methanol. In this invention, if the concentration of the modified polyamic acid solution is too low, film formation will be difficult during subsequent film-forming processes; if the concentration is too high, it will be difficult to remove internal solvent molecules and create pores during subsequent drying, also hindering film formation. Therefore, this invention controls the mass fraction of the solute in the modified polyamic acid solution to 1–40 wt%, preferably 10–30 wt%, more preferably 15–20 wt%. In some embodiments of this invention, the mixing of the modified polyamic acid and the solvent is preferably carried out under stirring conditions, the mixing temperature is 50–120°C, preferably 80–100°C, and the mixing time is 1–10 h, preferably 2–8 h. The mixing is preferably carried out in a sealed container, such as a blue-mouthed bottle.

[0080] After obtaining the modified polyamic acid solution, the present invention preferably composites it onto the surface of polyethersulfone through a film-forming treatment, and then performs imidization treatment on the obtained product and vacuum drying to obtain a composite membrane. In the present invention, the film-forming treatment can employ techniques well known to those skilled in the art, such as any one of electrospinning, spraying, blade coating, spin coating, hot pressing, gel stretching, or sol-gel methods. In some embodiments of the present invention, it is preferred to pour the modified polyamic acid solution onto a preheated substrate plate, using an aqueous polyethersulfone membrane as the substrate, and then perform film formation using any of the above-mentioned film-forming methods. The temperature of the preheated substrate plate is 25–85°C, preferably 30–60°C, and the substrate plate includes, but is not limited to, any one of glass plates, polymer plates, metal plates, or ceramic plates. After the above film-forming treatment, the obtained product is subjected to imidization treatment according to the present invention. During imidization, the obtained product can be directly placed in a specific temperature environment, or the product can be placed in an environment and then subjected to programmed temperature increase to a specific temperature, which is 200–300°C, preferably 220–260°C. The placement time of the product in the specific temperature environment is 0.1–20 h, preferably 1–10 h. The imidization treatment is preferably carried out in an oven. After the above imidization treatment, according to the present invention, the imidized composite membrane is preferably dried to remove solvent and achieve pore formation. The drying is preferably vacuum drying, with a temperature of 40–100°C, preferably 45–80°C, and a time of 0.1–48 h, preferably 10–24 h. After drying, a composite membrane with uniform pore size and high porosity is obtained.

[0081] In some embodiments of the present invention, when the PI is introduced in the form of modified polyimide, the method for preparing the composite separator includes the following steps:

[0082] S1: Mix the modified polyimide with a solvent to obtain a modified polyimide solution;

[0083] The modified polyimide is a norbornene-terminated polyimide or a polyaminobismaleimide;

[0084] S2: The modified polyimide solution is laminated onto the surface of the polyethersulfone membrane through a film-forming treatment, and then vacuum dried to obtain a composite membrane.

[0085] According to the present invention, the modified polyimide is first mixed with a solvent to obtain a modified polyimide solution. In the present invention, the modified polyimide is a norbornene-terminated polyimide or a polyaminobismaleimide. The present invention does not impose any particular limitation on the preparation method of the modified polyimide being a norbornene-terminated polyimide or a polyaminobismaleimide; it can be prepared according to methods well known to those skilled in the art. For example, in some embodiments of the present invention, monomers such as dialkyl esters of aromatic tetracarboxylic acids, aromatic diamines, and monoalkyl esters of 5-norbornene-2,3-dicarboxylic acids are dissolved in an alkyl alcohol (including but not limited to methanol or ethanol) at 40–70°C, preferably 60°C, for 4–8 hours, preferably 6 hours, to obtain a PMR-type norbornene-terminated modified polyimide. In some embodiments of the present invention, maleic anhydride and an aromatic diamine are reacted at 60–80°C, preferably 65°C, for 3–6 hours, preferably 4 hours, to generate polyaminobismaleimide. In the present invention, the molecular weight of the modified polyimide is preferably 500–100,000 g / mol, more preferably 2,000–10,000 g / mol. The solvent includes, but is not limited to, any one or more of N,N-dimethylacetamide, N-methylpyrrolidone, N,N-dimethylformamide, sulfolane, acetonitrile, tetrahydrofuran, acetone, toluene, chloroform, or methanol. In the present invention, if the concentration of the modified polyimide solution is too low, film formation will be difficult during subsequent film-forming processes; if the concentration is too high, it will be difficult to remove internal solvent molecules to create pores during subsequent drying processes, also hindering film formation. Therefore, the present invention controls the mass fraction of the solute in the modified polyimide solution to be 1–40 wt%, preferably 10–30 wt%, more preferably 15–20 wt%. In some embodiments of the present invention, the mixing of the modified polyimide and the solvent is preferably carried out under stirring conditions, the mixing temperature is 50–120°C, preferably 80–100°C, and the mixing time is 1–10 h, preferably 2–8 h. The mixing is preferably carried out in a sealed container, such as a blue-necked bottle.

[0086] In this invention, the film-forming treatment and drying steps in this method are consistent with the relevant content in the preparation method of the composite separator when the PI is introduced in the form of modified polyamic acid. To avoid complexity, they will not be described in detail here.

[0087] The method for preparing the composite membrane provided by this invention is simple. Using a polyethersulfone (PES) membrane as a substrate, modified polyimide is composited onto the surface of the PES membrane using conventional film-forming methods. Then, the solvent is removed by vacuum drying to achieve pore formation, resulting in a composite membrane with high porosity. In this invention, the preferred mass ratio of PI to PES in the formed PES / PI composite membrane is (0.1–1000):1, and the preferred molecular weight of PI is 2000. This preparation method requires no expensive equipment, has low processing costs, is easy to operate, and is simple to implement, possessing broad application prospects and facilitating large-scale industrial production.

[0088] The aqueous polyethersulfone / modified polyimide composite separator provided by this invention exhibits higher dimensional thermal stability and rigidity. The aqueous polyethersulfone has a glass transition temperature of 225°C and a heat distortion temperature of 203°C. Its mechanical properties remain essentially unchanged at 200°C, and it demonstrates excellent creep resistance and dimensional stability at high temperatures. After reinforcement with modified polyimide polymer composite, the deformation under high load at 300°C for one month is less than 0.003%, demonstrating excellent high-temperature dimensional stability, making it suitable for use in secondary batteries in special high-temperature environments. If a 50% reduction in tensile strength is considered as the continuous service life, the aqueous polyethersulfone can be used for 20 years at 180°C and for 5 years at 200°C. Therefore, the long-term service temperature of the aqueous polyethersulfone is 180°C, while the long-term service temperature can be increased to 230°C after adding modified polyimide polymer composite. Further tests on the prepared composite separator revealed that its liquid retention rate is between 200% and 1000%, exhibiting excellent wettability and thus addressing the viscosity requirements of electrolytes in secondary batteries to some extent. Its limiting oxygen index is greater than 40, demonstrating excellent flame retardancy and significantly improving the safety performance of secondary batteries. Furthermore, its tensile strength is above 95 MPa, exhibiting excellent mechanical properties. Taking lithium-ion batteries as an example, it can effectively suppress and resist lithium dendrite puncture (as tested in lithium-lithium deposition experiments), thereby avoiding short circuits caused by lithium dendrite punctures in traditional polyolefin separators.

[0089] Based on the superior performance of the aforementioned composite separator, this invention provides a liquid secondary battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte; the separator is the composite separator described in the above technical solution. The liquid secondary battery is selected from any one of lithium (sodium)-ion batteries, lithium (sodium) metal batteries, or lithium (sodium) sulfur batteries. In this invention, the positive electrode comprises a positive current collector and a positive electrode active material, and the negative electrode comprises a negative current collector and a negative electrode active material. The positive current collector is aluminum foil, and the negative current collector is copper foil. The active materials of the positive and negative electrodes vary depending on the type of liquid secondary battery. For example, in lithium metal batteries, lithium manganese oxide or high-nickel single-crystal 9055 can be used as the positive electrode, and lithium as the negative electrode; in lithium-ion batteries, lithium cobalt oxide, lithium iron phosphate, or lithium manganese oxide can be used as the positive electrode, and graphite, silicon-carbon, or lithium titanate as the negative electrode; in lithium-sulfur batteries, carbon-sulfur or polyacrylonitrile / sulfur can be used as the positive electrode, and lithium as the negative electrode. For example, sodium metal batteries can use sodium iron phosphate, sodium titanium phosphate, sodium iron pyrophosphate, sodium iron sulfate, sodium iron manganese phosphate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium fluorovanadium phosphate, or sodium vanadium phosphate as the positive electrode, and sodium as the negative electrode; sodium ion batteries can use any one of sodium iron pyrophosphate, sodium iron sulfate, or sodium vanadium phosphate as the positive electrode, and any one of sodium titanium phosphate, hard carbon, or sodium vanadium phosphate as the negative electrode; sodium-sulfur batteries can use carbon-sulfur or polyacrylonitrile / sulfur as the positive electrode, and sodium as the negative electrode.

[0090] This invention also provides a solid-liquid hybrid secondary battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte; the separator is the composite separator involved in the above-mentioned technical solution; the positive electrode comprises a positive electrode current collector, a positive electrode active material, and a solid electrolyte; the negative electrode comprises a negative electrode current collector, a negative electrode active material, and a solid electrolyte. The solid-liquid hybrid secondary battery is selected from any one of sodium (lithium)-ion batteries, sodium (lithium) metal batteries, or sodium (lithium) sulfur batteries. In this invention, the positive electrode current collector is aluminum foil; the negative electrode current collector is any one of aluminum foil, copper foil, or titanium foil. The solid electrolytes in the positive and negative electrodes are each independently any one of LLTO, LLZO, NZSP, boehmite, cryolite, or β-alumina. The active materials of the positive and negative electrodes vary depending on the type of solid-liquid hybrid secondary battery. The selection of the active materials of the positive and negative electrodes of the sodium (lithium)-ion battery, sodium (lithium) metal battery, or sodium (lithium) sulfur battery is as described in the relevant content of the above-mentioned technical solution and will not be repeated here.

[0091] It should be noted that in a solid-liquid hybrid secondary battery, the solid electrolyte can be mixed into the positive (or negative) electrode slurry or directly coated onto the positive (or negative) electrode sheet.

[0092] The electrolytes in the aforementioned liquid secondary batteries and solid-liquid hybrid secondary batteries are standard electrolytes well-known to those skilled in the art. The solvents include ethylene carbonate (EC), propylene carbonate (PC), and dimethyl carbonate (DMC), and the electrolyte salt is hexafluorophosphate. In this invention, the volume ratio of EC, PC, and DMC is preferably (1-2):(1-2):(1-2), more preferably 1:1:1. In this invention, the mass fraction of the solvent in the standard electrolyte is preferably 11-15%, more preferably 13%; the mass fraction of the electrolyte salt is 85-89%, more preferably 87%. Taking a lithium-ion battery containing the above-mentioned composite separator as an example, the lithium-ion battery was placed in a high-temperature environment of 300°C for 4 hours. It was found that the battery did not exhibit combustion or explosion, further verifying that the composite separator provided by this invention has excellent high-temperature thermal stability.

[0093] To further illustrate the present invention, detailed descriptions are provided below through the following embodiments. The experimental materials used in the following embodiments of the present invention are all commercially available products. The electrolytes used in the following embodiments are all standard commercial electrolytes for the corresponding secondary batteries. Specifically, the electrolytes for lithium-ion batteries, lithium metal batteries, and lithium-sulfur batteries are EC / PC / DMC + lithium hexafluorophosphate in a volume ratio of 1:1:1, with EC / PC / DMC having a mass fraction of 13% and lithium hexafluorophosphate having a mass fraction of 87%; the electrolytes for sodium-ion batteries, sodium metal batteries, and sodium-sulfur batteries are EC / PC / DMC + sodium hexafluorophosphate in a volume ratio of 1:1:1, with EC / PC / DMC having a mass fraction of 13% and lithium hexafluorophosphate having a mass fraction of 87%.

[0094] Preparation Example 1

[0095] This preparation example provides a norbornene-terminated polyamic acid, which is prepared by the following method:

[0096] S1: Norbornene anhydride and ethanol are refluxed at 55°C for 12 hours to produce a chemical reaction, wherein the amount of ethanol is 10 times that of norbornene anhydride, to obtain norbornene monoester monoacid.

[0097] S21: After dissolving the norbornene monoester monoacid in DMF, add an aromatic diamine under nitrogen protection and stir at room temperature for 1 hour.

[0098] The mass ratio of DMF to norbornene monoester monoacid is 3:1, and the molar ratio of norbornene monoester monoacid to aromatic diamine is preferably 1.5:1.

[0099] S22: Add acetic anhydride and pyridine (acetic anhydride to norbornene monoester monoacid 3:1, preferably 2:1 molar ratio of acetic anhydride to pyridine) to the reaction system of S21, and heat to 150℃ for 3 hours. Then, cool the resulting reaction solution to room temperature and pour it into 10 times its volume of deionized water. A yellow powdery solid precipitates out. After filtration, the filter cake is dried in a vacuum oven at 100℃ for 12 hours to obtain norbornene-terminated polyamic acid.

[0100] Preparation Example 2

[0101] This preparation example provides a polyaminoamic acid, which is prepared by referring to the method of Preparation Example 1, except that norbornene anhydride is replaced with quaternary ammonium salt-treated bismaleic anhydride, and other parameters and steps are consistent with those of Example 1.

[0102] Preparation Example 3

[0103] This preparation example provides a norbornene-terminated polyimide, which is prepared by a one-pot method, specifically including the following steps:

[0104] Monomers such as dialkyl esters of aromatic tetracarboxylic acids, aromatic diamines, and monoalkyl esters of 5-norbornene-2,3-dicarboxylic acids were weighed out at a molar ratio of 1:1.2:0.2 and dissolved in methanol at 60°C (the total mass of the above monomers to the mass ratio of methanol was 1:15) for 6 hours to obtain PMR-type norbornene-terminated polyimide.

[0105] Preparation Example 4

[0106] This preparation example provides a polyaminobismaleimide, which is prepared by the following method:

[0107] Maleic anhydride and aromatic diamine were weighed at a molar ratio of 1:1.2 and reacted at 65°C for 4 hours to produce polyaminobismaleimide.

[0108] Example 1

[0109] 0.3 g of norbornene-terminated polyamic acid obtained in Preparation Example 1 and 2.2 g of N-methylpyrrolidone were added to a 20 mL volumetric flask and stirred at 120 °C for 4 h to prepare a transparent 13.6 wt% polyamic acid solution. A composite membrane was prepared by electrospinning using an aqueous polyethersulfone membrane as a substrate. The obtained composite membrane was placed on a glass plate preheated at 50 °C and heated to 240 °C for imidization treatment for 2 h. The glass plate with the membrane was then placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a fully reacted PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0110] Figure 1The image shown is a scanning electron microscope image of the composite porous membrane obtained in Example 1, which shows that it has a porous structure.

[0111] Figure 2 The graph shows a comparison of the dimensional thermal stability of the composite porous membrane obtained in Example 1 and the commercial PP membrane at 180°C. It can be seen that the composite porous membrane provided by the present invention has better dimensional thermal stability than the commercial PP membrane.

[0112] Figure 3 The graph shows a comparison of the wetting performance of the composite porous membrane obtained in Example 1 and the commercial PP membrane in a commercial non-aqueous electrolyte (EC / DMC = 1:1 LIPF6-1M). It can be seen that the composite porous membrane provided by this invention is completely wetted by the solvent droplets, while the commercial PP membrane exhibits a significant wetting angle. This indicates that the composite porous membrane provided by this invention has excellent wettability.

[0113] The aforementioned composite porous membrane was assembled into a lithium metal battery using lithium manganese oxide as the positive electrode and lithium as the negative electrode. The lithium metal battery was allowed to stand at room temperature for 2 hours to allow the composite porous membrane to be fully impregnated, ultimately yielding a high-voltage lithium metal battery.

[0114] The high-voltage lithium metal battery obtained above was subjected to cycle performance testing at 1C. The test results are as follows: Figure 4 As shown, the high-voltage lithium metal battery exhibits excellent cycle performance at 1C (calculated capacity retention of 87.2% after 100 cycles) and an average coulombic efficiency as high as 99.6%. These results demonstrate that the composite porous membrane described above can significantly improve the coulombic efficiency and long-cycle stability of high-voltage lithium metal batteries.

[0115] Example 2

[0116] 0.4 g of the norbornene-terminated polyimide obtained in Preparation Example 3 and 2.9 g of N-methylpyrrolidone were added to a 20 mL volumetric flask and stirred at 100 °C for 8 h to prepare a transparent 13.7 wt% polyimide solution. The solution was poured onto a glass plate preheated to 25 °C, and a solution film was formed by coating an aqueous polyethersulfone membrane onto the substrate using a 400 μm doctor blade. After standing for 60 h, the glass plate with the solution film was placed in a vacuum oven at 70 °C and allowed to stand for 48 h to obtain a PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0117] The aforementioned composite porous membrane was assembled onto a high-nickel single-crystal 9055 as the positive electrode and lithium as the negative electrode to form a lithium metal battery. The lithium metal battery was left to stand at room temperature for 2 hours to allow the composite porous membrane to be fully impregnated, ultimately yielding a high-voltage lithium metal battery.

[0118] Referring to the method of Example 1, the high-voltage lithium metal battery obtained in this invention was subjected to cycle performance testing at 1C, and the test results were similar to those of Example 1.

[0119] Example 3

[0120] 0.2 g of the norbornene-terminated polyimide obtained in Preparation Example 3 and 1.7 g of N,N-dimethylformamide were added to a 20 mL volumetric flask and stirred at 110 °C for 6 h to prepare a transparent 11.8 wt% polyimide solution. The solution was poured onto a glass plate preheated to 85 °C, and a solution film was formed by coating an aqueous polyethersulfone membrane onto the substrate using a 400 μm doctor blade. After standing for 48 h, the glass plate with the solution film was placed in a vacuum oven at 45 °C and allowed to stand for 48 h to obtain a PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0121] The aforementioned composite porous membrane was assembled onto a high-nickel single-crystal 9055 as the positive electrode and lithium as the negative electrode to form a lithium metal battery. The lithium metal battery was left to stand at room temperature for 2 hours to allow the composite porous membrane to be fully impregnated, ultimately yielding a high-voltage lithium metal battery.

[0122] The voltage-to-capacity curves of the above-mentioned high-voltage lithium metal batteries were measured at 1C, and the results are as follows: Figure 5 As shown, the high-voltage lithium metal battery exhibits excellent performance at 1C with minimal polarization voltage change. The results demonstrate that this composite porous membrane can significantly improve the coulombic efficiency and cycle stability of high-voltage lithium metal batteries.

[0123] Example 4

[0124] 0.3 g of the polyamic acid obtained in Preparation Example 2 and 2.3 g of N,N-dimethylacetamide were added to a 20 mL volumetric flask and stirred at 100 °C for 5 h to prepare a transparent 13.0 wt% polyamic acid solution. A composite membrane was prepared by electrospinning with an aqueous polyethersulfone membrane as the substrate. The obtained composite membrane was placed on a glass plate preheated at 50 °C and then subjected to imidization treatment at 200 °C for 10 h. The glass plate with the membrane was then placed in a vacuum oven at 100 °C and allowed to stand for 0.1 h to obtain a fully reacted PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0125] The aforementioned composite separator was assembled into a lithium-ion battery using lithium cobalt oxide as the positive electrode and graphite as the negative electrode. The lithium-ion battery was left to stand at room temperature for 2 hours to allow for full impregnation, ultimately yielding a high-voltage lithium-ion battery.

[0126] Referring to the method of Example 1, the high-voltage lithium-ion battery obtained by the present invention was subjected to cycle performance testing at 1C. It was calculated that after 100 cycles, the capacity retention rate was 93.2%, and the average coulombic efficiency was above 99.7%.

[0127] Example 5

[0128] 0.1 g of the polyaminobismaleimide obtained in Preparation Example 4 and 1.2 g of sulfolane were added to a 20 mL volumetric flask and stirred at 80 °C for 7 h to prepare a transparent 8.3 wt% polyimide solution. The solution was poured onto a glass plate preheated to 60 °C and coated with a solution membrane using a 400 μm doctor blade, using an aqueous polyethersulfone membrane as a carrier. After standing for 84 h, the glass plate with the solution membrane was placed in a vacuum oven at 45 °C and allowed to stand for 4 h to obtain a PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0129] The aforementioned composite porous membrane was assembled into a lithium-ion battery using lithium iron phosphate as the positive electrode and silicon-carbon as the negative electrode. The lithium-ion battery was left to stand at room temperature for 2 hours to allow it to fully impregnate, ultimately yielding a high-voltage lithium-ion battery.

[0130] Referring to the method of Example 1, the high-voltage lithium-ion battery obtained in this invention was subjected to cycle performance testing at 1C, and the test results were similar to those of Example 5.

[0131] Example 6

[0132] 0.3 g of the polyaminobismaleimide obtained in Preparation Example 4, 1.3 g of N-methylpyrrolidone, and 1.3 g of N,N-dimethylacetamide were added to a 20 mL volumetric flask and stirred at 95 °C for 3 h to prepare a transparent 11.5 wt% polyimide solution. The solution was poured onto a glass plate preheated to 70 °C, and a solution membrane was coated using a 400 μm doctor blade with an aqueous polyethersulfone membrane as a carrier. After standing for 60 h, the glass plate with the solution membrane was placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0133] The aforementioned composite porous membrane was assembled into a lithium-ion battery using lithium manganese oxide as the positive electrode and lithium titanate as the negative electrode. The lithium-ion battery was left to stand at room temperature for 2 hours to allow it to fully impregnate, ultimately yielding a high-voltage aqueous lithium-ion battery.

[0134] Referring to the method of Example 1, the high-voltage lithium-ion battery obtained in this invention was subjected to cycle performance testing at 1C, and the test results were similar to those of Example 5.

[0135] Example 7

[0136] 0.1 g of the polyaminobismaleimide obtained in Preparation Example 4, 1.3 g of sulfolane, and 1.3 g of N,N-dimethylformamide were added to a 20 mL volumetric flask and stirred at 105 °C for 2 h to prepare a transparent 3.8 wt% polyimide solution. The solution was poured onto a glass plate preheated to 40 °C, and a solution membrane was coated using a 400 μm doctor blade with an aqueous polyethersulfone membrane as a carrier. After standing for 72 h, the glass plate with the solution membrane was placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a PES / PI composite porous membrane (the mass ratio of PI to PES was 15:1, and the molecular weight of PI was 2000).

[0137] The aforementioned composite porous membrane was assembled into a sodium metal battery using sodium vanadium phosphate as the positive electrode and sodium as the negative electrode. The sodium metal battery was allowed to stand at room temperature for 2 hours to allow it to be fully wetted, ultimately yielding a high-voltage sodium metal battery.

[0138] Referring to the method of Example 1, the high-voltage sodium metal battery obtained by the present invention was subjected to cycle performance testing at 1C. It was calculated that after 100 cycles, the capacity retention rate was 95.7%, and the average coulombic efficiency was above 99.8%.

[0139] Example 8

[0140] 0.2 g of norbornene-terminated polyamic acid obtained in Preparation Example 1, 1.1 g of N,N-dimethylformamide, and 1.1 g of N,N-dimethylacetamide were added to a 20 mL volumetric flask and stirred at 135 °C for 2 h to prepare a transparent 9.1 wt% polyamic acid solution. The solution was poured onto a glass plate preheated to 50 °C and coated with a solution membrane using a 400 μm doctor blade, using an aqueous polyethersulfone membrane as a carrier. After standing for 48 h, the glass plate with the solution membrane was placed in a 250 °C oven for imidization treatment for 2 h. Then, the product was placed in a 45 °C vacuum oven and allowed to stand for 12 h to finally obtain a fully reacted PES / PI composite porous membrane (PI to PES mass ratio of 15:1, PI molecular weight of 2000).

[0141] A sodium-vanadium phosphate battery was constructed using the aforementioned composite separator as the positive electrode and sodium-vanadium phosphate as the negative electrode. The battery was allowed to stand at room temperature for 2 hours to allow for full wetting, ultimately yielding a high-voltage aqueous sodium-ion battery.

[0142] Referring to the method of Example 1, the high-voltage sodium-ion battery obtained by the present invention was subjected to cycle performance testing at 1C. It was calculated that after 200 cycles, the capacity retention rate was 89%, and the average coulombic efficiency was above 99.3%.

[0143] Example 9

[0144] 0.3 g of norbornene-terminated polyimide obtained in Preparation Example 3, 0.7 g of N-methylpyrrolidone, 0.7 g of N,N-dimethylformamide, and 0.7 g of sulfolane were added to a 20 mL volumetric flask and stirred at 140 °C for 3 h to prepare a transparent 14.3 wt% polyimide solution. A composite membrane was prepared by electrospinning using an aqueous polyethersulfone membrane as a carrier. The membrane was placed in a vacuum oven at 45 °C and allowed to stand for 24 h to obtain a PES / PI composite porous membrane (the mass ratio of PI to PES was 15:1, and the molecular weight of PI was 2000).

[0145] The aforementioned composite porous membrane was assembled into a lithium-sulfur battery using polyacrylonitrile / sulfur as the positive electrode and lithium as the negative electrode. The lithium-sulfur battery was allowed to stand at room temperature for 2 hours to allow it to be fully wetted, ultimately yielding a high-voltage lithium-sulfur battery.

[0146] Referring to the method of Example 1, the high-voltage lithium-sulfur battery obtained by the present invention was subjected to cycle performance testing at 1C. It was calculated that after 300 cycles, the capacity retention rate was 82.9%, and the average coulombic efficiency was above 99.4%.

[0147] Example 10

[0148] 0.3 g of the norbornene-terminated polyamic acid salt obtained in Preparation Example 1, 0.7 g of sulfolane, 0.7 g of N,N-dimethylformamide, and 0.7 g of N,N-dimethylacetamide were added to a 20 mL volumetric flask and stirred at 115 °C for 4 h to prepare a transparent 14.36 wt% polyimide-polyamic acid solution. A composite membrane was initially prepared using electrospinning with an aqueous polyethersulfone membrane as the substrate. The composite membrane was then subjected to imidization treatment in a 250 °C oven for 8 h, followed by standing in a 45 °C vacuum oven for 12 h to obtain a fully reacted PES / PI composite porous membrane (PI to PES mass ratio of 15:1, PI molecular weight of 2000).

[0149] A sodium metal battery was constructed using the aforementioned composite porous membrane as the positive electrode and sodium as the negative electrode, assembled with sodium vanadium fluorophosphate. The sodium metal battery was allowed to stand at room temperature for 2 hours to allow for full wetting, ultimately yielding a high-voltage sodium metal battery.

[0150] Referring to the method of Example 1, the high-voltage sodium metal battery obtained by the present invention was subjected to cycle performance testing at 1C, and the test results were similar to those of Example 7.

[0151] Example 11

[0152] 0.15 g of the polyaminobismaleimide obtained in Preparation Example 4, 1.35 g of sulfolane, and 1.35 g of N,N-dimethylformamide were added to a 20 mL volumetric flask and stirred at 105 °C for 2 h to prepare a transparent 5.6 wt% polyimide solution. Using aqueous polyethersulfone as a carrier, the solution was poured onto a glass plate preheated to 60 °C and coated with a 400 μm doctor blade to form a solution film. After standing for 72 h, the glass plate with the solution film was placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a PES / PI composite porous membrane (the mass ratio of PI to PES was 15:1, and the molecular weight of PI was 2000).

[0153] The aforementioned composite porous membrane was assembled into a sodium-sulfur battery using polyacrylonitrile / sulfur as the positive electrode and sodium as the negative electrode. The battery was allowed to stand at room temperature for 2 hours to allow for full wetting, ultimately yielding a high-voltage sodium-sulfur battery.

[0154] Example 12

[0155] 0.3 g of the polyaminobismaleimide obtained in Preparation Example 4 and 2.2 g of N-methylpyrrolidone were added to a 20 mL volumetric flask and stirred at 120 °C for 4 h to prepare a transparent 13.6 wt% polyimide solution. The solution was then electrospinned onto a composite membrane with aqueous polyethersulfone as the carrier. The membrane was placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a PES / PI composite porous membrane (the mass ratio of PI to PES was 15:1, and the molecular weight of PI was 2000).

[0156] The aforementioned composite separator was assembled into a sodium metal battery using sodium vanadium phosphate as the positive electrode and sodium as the negative electrode. The sodium metal battery was left to stand at room temperature for 2 hours to allow it to fully impregnate, ultimately yielding a high-voltage sodium metal battery.

[0157] The high-voltage sodium metal battery obtained above was subjected to cycle performance testing at 1C, and the results are as follows: Figure 6 As shown, the high-voltage sodium metal battery exhibits excellent cycle performance at 1C (capacity retention of 96.35% after 500 cycles) and a stable coulombic efficiency of up to 99.7%. These results demonstrate that the polyimide separator can significantly improve the coulombic efficiency and long-cycle stability of high-voltage lithium metal batteries.

[0158] Example 13

[0159] 0.3 g of the polyaminoamic acid obtained in Preparation Example 2 and 2.2 g of N-methylpyrrolidone were added to a 20 mL volumetric flask and stirred at 120 °C for 4 h to prepare a transparent 13.6 wt% polyimide solution. The solution was then electrospinned onto an aqueous polyethersulfone membrane. The membrane was placed in a 250 °C vacuum oven and allowed to stand for 12 h for imidization treatment. The membrane was then placed in a 45 °C vacuum oven and allowed to stand for 12 h to finally obtain a PES / PI composite porous membrane (the mass ratio of PI to PES was 15:1, and the molecular weight of PI was 2000).

[0160] The aforementioned composite porous membrane was assembled into a sodium-ion battery using sodium vanadium fluoride phosphate as the positive electrode and sodium vanadium phosphate as the negative electrode. The sodium metal battery was allowed to stand at room temperature for 2 hours to allow it to be fully impregnated, ultimately yielding a high-voltage sodium metal battery.

[0161] The high-voltage sodium-ion battery obtained above was subjected to cycle performance testing at 1C. Results Figure 7 As shown, Figure 7 The long-cycle performance of sodium vanadium fluoride phosphate / sodium-ion batteries assembled with this separator was evaluated. It can be seen that the high-voltage sodium-ion battery exhibits excellent cycle performance at 1C (capacity retention of 85.3% after 300 cycles, calculated based on the highest capacity within 300 cycles, excluding the first cycle), and an average coulombic efficiency exceeding 99.1%. The results indicate that this polyimide separator can significantly improve the coulombic efficiency and long-cycle stability of high-voltage sodium-ion batteries.

[0162] Example 14

[0163] 0.3 g of norbornene-terminated polyamic acid obtained in Preparation Example 1 and 2.2 g of N-methylpyrrolidone were added to a 20 mL volumetric flask and stirred at 120 °C for 4 h to prepare a transparent 13.6 wt% polyamic acid solution. A composite membrane was prepared by electrospinning using an aqueous polyethersulfone membrane as a substrate. The obtained composite membrane was placed on a glass plate preheated at 50 °C and heated to 240 °C for imidization treatment for 2 h. The glass plate with the membrane was then placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a fully reacted PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0164] The aforementioned composite porous membrane was assembled into a lithium metal battery using high-nickel single-crystal 9055 as the positive electrode and lithium as the negative electrode. The surface of the high-nickel single-crystal 9055 positive electrode material was optimized by coating it with a layer of lithium lanthanum titanium oxide solid electrolyte mixed with conductive carbon. The lithium metal battery was allowed to stand at room temperature for 2 hours to fully impregnate the composite porous membrane, ultimately yielding a high-voltage lithium metal battery.

[0165] Referring to the method of Example 1, the high-voltage lithium metal battery obtained in this invention was subjected to cycle performance testing at 1C, and the test results were similar to those of Example 2.

[0166] Example 15

[0167] 0.3 g of norbornene-terminated polyamic acid obtained in Preparation Example 1 and 2.2 g of N-methylpyrrolidone were added to a 20 mL volumetric flask and stirred at 120 °C for 4 h to prepare a transparent 13.6 wt% polyamic acid solution. A composite membrane was prepared by electrospinning using an aqueous polyethersulfone membrane as a substrate. The obtained composite membrane was placed on a glass plate preheated at 50 °C and heated to 240 °C for imidization treatment for 2 h. The glass plate with the membrane was then placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a fully reacted PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0168] The aforementioned composite porous membrane was assembled into a lithium-ion battery using lithium cobalt oxide as the positive electrode and graphite as the negative electrode. The lithium cobalt oxide positive electrode material was optimized by coating its surface with a lithium lanthanum zirconium oxide solid electrolyte doped with conductive carbon. The lithium metal battery was allowed to stand at room temperature for 2 hours to fully impregnate the composite porous membrane, ultimately yielding a high-voltage lithium-ion battery.

[0169] Referring to the method of Example 1, the high-voltage lithium-ion battery obtained in this invention was subjected to cycle performance testing at 1C, and the test results were similar to those of Example 3.

[0170] Example 16

[0171] 0.3 g of norbornene-terminated polyamic acid obtained in Preparation Example 1 and 2.2 g of N-methylpyrrolidone were added to a 20 mL volumetric flask and stirred at 120 °C for 4 h to prepare a transparent 13.6 wt% polyamic acid solution. A composite membrane was prepared by electrospinning using an aqueous polyethersulfone membrane as a substrate. The obtained composite membrane was placed on a glass plate preheated at 50 °C and heated to 240 °C for imidization treatment for 2 h. The glass plate with the membrane was then placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a fully reacted PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0172] The aforementioned composite porous membrane was assembled into a lithium-ion battery using lithium iron manganese phosphate as the positive electrode and graphite as the negative electrode. The lithium iron manganese phosphate positive electrode material was optimized by coating its surface with a layer of boehmite solid electrolyte mixed with conductive carbon. The lithium metal battery was allowed to stand at room temperature for 2 hours to fully impregnate the composite porous membrane, ultimately yielding a high-voltage lithium-ion battery.

[0173] Referring to the method of Example 1, the high-voltage lithium-ion battery obtained in this invention was subjected to cycle performance testing at 1C, and the test results were similar to those of Example 4.

[0174] Example 17

[0175] 0.3 g of norbornene-terminated polyamic acid obtained in Preparation Example 1 and 2.2 g of N-methylpyrrolidone were added to a 20 mL volumetric flask and stirred at 120 °C for 4 h to prepare a transparent 13.6 wt% polyamic acid solution. A composite membrane was prepared by electrospinning using an aqueous polyethersulfone membrane as a substrate. The obtained composite membrane was placed on a glass plate preheated at 50 °C and heated to 240 °C for imidization treatment for 2 h. The glass plate with the membrane was then placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a fully reacted PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0176] The aforementioned composite porous membrane was assembled in a sodium metal battery using sodium vanadium phosphate as the positive electrode and metallic sodium as the negative electrode. Specifically, the surface of the sodium vanadium phosphate positive electrode material was coated with a layer of NZSP (Na3Zr2Si2PO4) doped with conductive carbon. 12 The solid electrolyte was optimized and modified. The sodium metal battery was left to stand at room temperature for 2 hours to fully impregnate the composite porous membrane, and finally a high-voltage sodium metal battery was obtained.

[0177] Referring to the method of Example 1, the high-voltage sodium metal battery obtained by the present invention was subjected to cycle performance testing at 1C, and the test results were similar to those of Example 7.

[0178] Example 18

[0179] 0.3 g of norbornene-terminated polyamic acid obtained in Preparation Example 1 and 2.2 g of N-methylpyrrolidone were added to a 20 mL volumetric flask and stirred at 120 °C for 4 h to prepare a transparent 13.6 wt% polyamic acid solution. A composite membrane was prepared by electrospinning using an aqueous polyethersulfone membrane as a substrate. The obtained composite membrane was placed on a glass plate preheated at 50 °C and heated to 240 °C for imidization treatment for 2 h. The glass plate with the membrane was then placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a fully reacted PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0180] The aforementioned composite porous membrane was assembled into a sodium-ion battery using sodium ferric sulfate as the positive electrode and hard carbon as the negative electrode. The sodium ferric sulfate positive electrode material was optimized by coating its surface with a layer of cryolite (Na3AlF6) solid electrolyte mixed with conductive carbon. The sodium-ion battery was allowed to stand at room temperature for 2 hours to fully impregnate the composite porous membrane, ultimately yielding a high-voltage lithium-ion battery.

[0181] Referring to the method of Example 1, the high-voltage lithium-ion battery obtained in this invention was subjected to cycle performance testing at 1C, and the test results were similar to those of Example 8.

[0182] Example 19

[0183] 0.3 g of norbornene-terminated polyamic acid obtained in Preparation Example 1 and 2.2 g of N-methylpyrrolidone were added to a 20 mL volumetric flask and stirred at 120 °C for 4 h to prepare a transparent 13.6 wt% polyamic acid solution. A composite membrane was prepared by electrospinning using an aqueous polyethersulfone membrane as a substrate. The obtained composite membrane was placed on a glass plate preheated at 50 °C and heated to 240 °C for imidization treatment for 2 h. The glass plate with the membrane was then placed in a vacuum oven at 45 °C and allowed to stand for 12 h to obtain a fully reacted PES / PI composite porous membrane (the mass ratio of PI to PES was 20:1, and the molecular weight of PI was 2000).

[0184] The aforementioned composite porous membrane was assembled into a sodium-ion battery using sodium iron pyrophosphate as the positive electrode and hard carbon as the negative electrode. The sodium iron pyrophosphate positive electrode material was optimized by coating its surface with a layer of β-alumina (Na₂O-(Al₂O₃)₅) solid electrolyte mixed with conductive carbon. The sodium-ion battery was allowed to stand at room temperature for 2 hours to fully impregnate the composite porous membrane, ultimately yielding a high-voltage sodium-ion battery.

[0185] Referring to the method of Example 1, the high-voltage lithium-ion battery obtained in this invention was subjected to cycle performance testing at 1C, and the test results were similar to those of Example 7.

[0186] Comparative Example 1

[0187] Commercially available PP 2500 diaphragm.

[0188] Comparative Example 2

[0189] The preparation method of a self-made unmodified thermoplastic polyimide separator is as follows:

[0190] Dissolve 3g of thermoplastic polyimide powder in 20mL of acetonitrile at 90℃, then coat it onto a polytetrafluoroethylene plate. After cooling to 25℃, the precipitate will be formed. Finally, the solvent will be evaporated in a vacuum oven at 45℃ to obtain the final product.

[0191] Comparative Example 3

[0192] Commercial polyethersulfone filter membranes.

[0193] Comparative Example 4

[0194] Self-made modified thermoplastic polyimide diaphragm.

[0195] The preparation method is the same as in Example 2. The obtained transparent polyimide solution can be directly coated into a film by scraping.

[0196] Performance Characterization

[0197] The performance of the composite porous membranes provided in Examples 1-19 and the diaphragms provided in Comparative Examples 1-4 was comprehensively characterized.

[0198] The corresponding characterization methods are as follows:

[0199] Thickness testing is performed using vernier calipers or a micrometer.

[0200] Aperture measurement involves estimating the average pore size using electron micrographs obtained from scanning electron microscopy.

[0201] Porosity testing was performed using a standard solvent – ​​n-butanol.

[0202] The solvent used in the liquid retention rate test was the standard commercial electrolyte involved in the above-mentioned secondary batteries;

[0203] Tensile strength is measured using a tensile strength tester;

[0204] The limiting oxygen index is determined using a standard candle test.

[0205] High-temperature mechanical properties were determined using a high-temperature drying oven.

[0206] The standard reagents used in the wettability test were the standard commercial electrolytes involved in the above-mentioned secondary batteries.

[0207] The characterization results are shown in Table 1:

[0208] Table 1

[0209]

[0210]

[0211] As shown in Table 1, the composite porous membrane provided by this invention has uniform pore size, high tensile strength, high liquid retention rate, good flame retardancy, and excellent dimensional thermal stability, fully meeting the requirements for secondary battery separators. The traditional commercial PP 2500 separator provided in Comparative Example 1 shrinks by 30% when heated to 150℃, exhibiting poor thermal stability, poor wettability and flame retardancy, and low liquid retention rate and tensile strength, thus failing to meet the requirements for secondary battery separators. The commercial polyethersulfone filter membrane provided in Comparative Example 3, while possessing excellent wettability and a good liquid retention rate, shrinks by 13% when heated to 150℃, exhibiting poor dimensional thermal stability and low tensile strength compared to polyimide separators, thus failing to meet the requirements for secondary battery separators. The self-made unmodified thermoplastic polyimide separator provided in Comparative Example 2, while possessing excellent wettability and high-temperature dimensional thermal stability, suffers from limited thickness due to the lack of carrier control and the absence of polyethersulfone composite assistance, resulting in a low liquid retention rate, thus failing to meet the requirements for secondary battery separators. The self-made modified thermoplastic polyimide separator provided in Comparative Example 4 has a limited thickness due to the lack of carrier regulation, and also has a low liquid retention rate due to the lack of polyethersulfone composite assistance, which fails to meet the requirements of secondary battery separators.

[0212] Electrochemical performance tests were conducted on the batteries obtained in the examples and comparative examples. The battery's first-cycle efficiency, average coulombic efficiency, capacity retention, and discharge specific capacity were characterized by the Wuhan Landian Tester; the DCR was detected by the electrochemical workstation.

[0213] The electrochemical performance characterization results are shown in Table 2:

[0214] Table 2

[0215]

[0216]

[0217] As shown in Table 2, the batteries provided in the examples all maintained a capacity retention rate of over 80% after 100 cycles, which is far superior to the comparative examples. This demonstrates the excellent ion transport capability of the composite separator provided by the present invention for lithium / sodium salts. In lithium iron phosphate / lithium metal batteries, the secondary battery using the composite separator has a higher coulombic efficiency compared to the comparative examples, reflecting the higher wettability of the composite separator in practical applications and its role in promoting the uniform deposition of lithium / sodium ions on the negative electrode.

[0218] Compared to the composite membrane provided by this invention, the commercially available PP2500 membrane in Comparative Example 1 has no advantage whatsoever, exhibiting significant differences in dimensional thermal stability, wettability, high-temperature mechanical properties, and limiting oxygen index. In Comparative Example 2, the unmodified thermoplastic polyimide membrane still exhibits certain deficiencies in electrochemical performance compared to the composite membrane. In Comparative Example 3, the commercially available polyethersulfone filter membrane shows a significant difference in electrochemical performance compared to the composite membrane, and can only be used as a carrier for coating modification. In Comparative Example 4, the modified thermoplastic polyimide membrane has a limited service life compared to the composite membrane and cannot be compatible with the excellent properties of the polyethersulfone composite carrier.

[0219] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A composite diaphragm, characterized in that, It includes a polyethersulfone film layer and a modified polyimide film layer disposed on the surface of the polyethersulfone film layer; The modified polyimide film is a norbornene-terminated polyimide film or a polyaminobismaleimide film.

2. The composite diaphragm according to claim 1, characterized in that, The mass ratio of the modified polyimide film to the polyethersulfone film is (0.1~1000):

1.

3. The composite diaphragm according to claim 1, characterized in that, The porosity of the composite membrane is 40-95%; The composite membrane has a pore size of 0.01–10 μm.

4. The composite diaphragm according to claim 1, characterized in that, The thickness of the composite diaphragm is 1–1000 μm.

5. The method for preparing the composite diaphragm according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1: Mix the modified polyamic acid with a solvent to obtain a modified polyamic acid solution; The modified polyamic acid is norbornene-terminated polyamic acid or polyaminoamic acid; S2: The modified polyamic acid solution is composited onto the surface of a polyethersulfone membrane through a film-forming treatment. The resulting product is then subjected to imidization treatment and vacuum drying to obtain a composite membrane.

6. The method for preparing the composite separator according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1: Mix the modified polyimide with a solvent to obtain a modified polyimide solution; The modified polyimide is a norbornene-terminated polyimide or a polyaminobismaleimide; S2: The modified polyimide solution is laminated onto the surface of the polyethersulfone membrane through a film-forming treatment, and then vacuum dried to obtain a composite membrane.

7. The preparation method according to claim 5, characterized in that, The modified polyamic acid has a molecular weight of 500–100,000 g / mol; The mass fraction of the solute in the modified polyamic acid solution is 1–40 wt%.

8. The preparation method according to claim 6, characterized in that, The modified polyimide has a molecular weight of 500–100,000 g / mol; The mass fraction of the solute in the modified polyimide solution is 1–40 wt%.

9. The preparation method according to claim 5 or 6, characterized in that, The solvent is selected from any one or more of N,N-dimethylacetamide, N-methylpyrrolidone, N,N-dimethylformamide, sulfolane, acetonitrile, tetrahydrofuran, acetone, toluene, chloroform, or methanol.

10. The preparation method according to claim 5 or 6, characterized in that, The mixing temperature is 50–150°C.

11. The preparation method according to claim 5 or 6, characterized in that, The film-forming treatment method is selected from any one of electrospinning, spraying, scraping, spin coating, hot pressing, gel stretching, or sol-gel methods.

12. The preparation method according to claim 5, characterized in that, The imidization treatment is performed at a temperature of 200–300°C for a time of 0.1–120 h.

13. The preparation method according to claim 5 or 6, characterized in that, The vacuum drying temperature is 40–100°C; the drying time is 0.1–48 h.

14. A liquid secondary battery, characterized in that, Includes positive electrode, negative electrode, membrane, and electrolyte; The diaphragm is the composite diaphragm according to any one of claims 1 to 4 or the composite diaphragm prepared by the preparation method according to any one of claims 5 to 13.

15. The liquid secondary battery according to claim 14, characterized in that, The liquid secondary battery is selected from any one of lithium-ion batteries, lithium metal batteries, lithium-sulfur batteries, sodium-ion batteries, sodium metal batteries, or sodium-sulfur batteries.

16. The liquid secondary battery according to claim 14, characterized in that, The positive electrode includes a positive electrode current collector and a positive electrode active material; The negative electrode includes a negative electrode current collector and an active material of the negative electrode.

17. The liquid secondary battery according to claim 14, characterized in that, The active material of the positive electrode is selected from any one of the following: high-nickel single crystal 9055, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, sodium iron phosphate, sodium titanium phosphate, sodium iron pyrophosphate, sodium iron sulfate, sodium iron manganese phosphate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium fluorovanadium phosphate, sodium vanadium phosphate, carbon sulfur, or polyacrylonitrile / sulfur. The positive current collector is aluminum foil; The active material of the negative electrode is selected from any one of lithium metal, graphite, silicon carbide, lithium titanate, hard carbon, sodium vanadium phosphate, sodium titanium phosphate, or sodium metal. The negative electrode current collector is copper foil.

18. A solid-liquid hybrid secondary battery, characterized in that, Includes positive electrode, negative electrode, membrane, and electrolyte; The diaphragm is the composite diaphragm according to any one of claims 1 to 4 or the composite diaphragm prepared by the preparation method according to any one of claims 5 to 13; The positive electrode includes a positive electrode current collector, a positive electrode active material, and a solid electrolyte; The negative electrode includes a negative electrode current collector, an active material of the negative electrode, and a solid electrolyte.

19. The solid-liquid hybrid secondary battery according to claim 18, characterized in that, The solid-liquid hybrid secondary battery is selected from any one of lithium-ion batteries, lithium metal batteries, lithium-sulfur batteries, sodium-ion batteries, sodium metal batteries, or sodium-sulfur batteries.

20. The solid-liquid hybrid secondary battery according to claim 18, characterized in that, The active material of the positive electrode is selected from any one of the following: high-nickel single crystal 9055, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, sodium iron phosphate, sodium titanium phosphate, sodium iron pyrophosphate, sodium iron sulfate, sodium iron manganese phosphate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium fluorovanadium phosphate, sodium vanadium phosphate, carbon sulfur, or polyacrylonitrile / sulfur. The positive current collector is aluminum foil; The active material of the negative electrode is selected from any one of lithium metal, graphite, silicon carbide, lithium titanate, hard carbon, sodium vanadium phosphate, sodium titanium phosphate, or sodium metal. The negative electrode current collector is any one of aluminum foil, copper foil, or titanium foil; The solid electrolytes in the positive and negative electrodes are each independently any one of LLTO, LLZO, NZSP, cryolite, boehmite, or β-alumina.

Citation Information

Patent Citations

  • Preparation method for crosslinked polyimide gel polymer electrolyte membrane

    CN106328862A

  • Separator having heat-resistant insulating layer

    CN103918104A

  • Nonaqueous electrolyte secondary battery

    CN105977413A